Introduction and 2024–2025 Update - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural identity; Economic Justice; Identity (music); Inclusion (mineral); Relevance (law); Work (physics); dept.dei

Moving Forward - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural center; Cultural diversity; Cultural identity; Identity (music); Multiculturalism; Politics; dept.dei

Preface - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: dept.dei

Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Emerald Group Publishing Ltd., 2025)
Heart Work: The Handbook on the Survival and Success of Cultural and Identity Centers in Higher Education highlights the experiences of higher education professionals working in these centers. This handbook offers a blend of personal stories and the latest research on cultural and identity centers, building on Dr. Lori Patton Davis’ 2010 book, Culture Centers in Higher Education: Perspectives on Identity, Theory, and Practice. Since 2010, these centers have navigated significant challenges, including the global COVID-19 pandemic, and have increased focus on institutional racism. The book delves into the experiences and histories of various cultural and identity centers, including Latinx/e Cultural Centers, Asian, Pacific Islander, Middle Eastern Arab and Desi Cultural Centers, Native American/Indigenous Cultural Centers, Black/African American Cultural Centers, Disability Cultural Centers, Lesbian, Gay, Bisexual, Transgender, Queer+ Centers, and Undocumented Student Resource Centers. In light of recent events affecting minoritized populations, it also covers topics such as evolving practices in cultural/identity centers, university politics, and strategies for practitioners to advance and sustain the Heart Work. Heart Work offers community members - especially potential and current practitioners, faculty, and staff in higher education - an understanding of the recent environmental context of cultural and identity centers. As our society evolves, recognizing that identities are not monolithic and embracing intersectionality allows for a deeper understanding of oppression and lived experiences. This handbook aims to bridge the gap by continuing the research and practice of cultural and identity centers in higher education. © 2026 by Emerald Publishing Limited. All rights reserved.
Keywords: dept.dei

Celebrating and Supporting Latinidad on College Campuses: Latinx/E Cultural Centers - Felix, Alex Romero; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Center (category theory); Cultural center; Higher education; Politics; Population; dept.dei

Supporting Native American/Indigenous Students’ Survivance Through Native American/Indigenous Cultural Centers - Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural diversity; Ethnic group; Indigenous; Native american; Traditional knowledge; White (mutation); dept.dei